DIETARY CORRECTION OF HYPERINSULINEMIA AND HEMOSTASIS PARAMETERS IN OVERWEIGHT ARTERIAL HYPERTENSION PATIENTS - Lizogub, V.G.; Kramarova, V.N.; Polonska, L.N.; Камінська, Т.М.; Melnychuk, I.O.; Tyravska, Y.V. (World of Medicine and Biology, 2020)
The purpose of our study was to investigate the influence of a carbohydrate-restricted diet up to 250 g per day for 12 weeks on body mass index, insulin level, and parameters of hemostasis in patients with arterial hypertension and metabolic disorders. It was registered the decrease in the body mass index by 7%, insulin level by 27.8%, factor von Willebrand activity (р=0.009) and soluble fibrin content (р=0.03) and the improvement of the platelet aggregation induced by ADP and ristocetin in patients with arterial hypertension and increased body mass index who followed the diet with carbohydrate restriction up to 250 g per day for 12 weeks in addition to standard therapy. A diet with carbohydrate restriction up to 250 g per day should be recommended to the patients with combination of arterial hypertension, increased body mass index and hyperinsulinemia in addition to antihypertensive therapy.
Keywords: arterial hypertension; carbohydrate-restricted diet; body mass index; insulin level; hemostasis parameters